2016
DOI: 10.1123/rsj.2015-0047
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Campus Recreational Sports: A Rasch Calibration

Abstract: The purpose of this study is to introduce Rasch analysis as a methodological advance in recreational sports research. Specifically, the Rasch technique is illustrated through its application to an empirical investigation of college students' perceived benefits from recreational sports participation. This study seeks to develop and calibrate sources of the Perceived Benefit Scale (PBS) for recreational sports participants at the college level using the Rasch model. Survey data from 940 students at a large publi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For example, if the analysis of the teaching data of table tennis elective course of public physical education in a university shows that students' interest in learning needs to be improved. In view of the needs of this curriculum reform, the school uses the intelligent teaching system to monitor students' interest in table tennis, compares table tennis teaching methods in different places, and carries out targeted reform on table tennis teaching in combination with the methods of cultivating students' interest [21]. For example, through the analysis of social employment demand, talent quality demand, and other major data, schools can obtain more targeted talent training indicators, pointing out the direction for public sports reform.…”
Section: Realizing the Integration And Intercommunication Of External Wisdommentioning
confidence: 99%
“…For example, if the analysis of the teaching data of table tennis elective course of public physical education in a university shows that students' interest in learning needs to be improved. In view of the needs of this curriculum reform, the school uses the intelligent teaching system to monitor students' interest in table tennis, compares table tennis teaching methods in different places, and carries out targeted reform on table tennis teaching in combination with the methods of cultivating students' interest [21]. For example, through the analysis of social employment demand, talent quality demand, and other major data, schools can obtain more targeted talent training indicators, pointing out the direction for public sports reform.…”
Section: Realizing the Integration And Intercommunication Of External Wisdommentioning
confidence: 99%
“…For instance, Kampf and Teske (2013) indicated that participation in university recreational sports activities contributes to acquiring skills for learning and preparation for professional life. This is supported by Kim et al (2016) suggestion that students who participate in university sports are more likely to transfer skills and character traits such as integrity, commitment, and work ethics learned from sports into their career fields. More benefits associated with sports participation by university students include; improved physical fitness, high self-esteem, better academic performance, and enhanced mental and social development (Coenders et al, 2017;Diehl et al, 2018;Forrester, 2015;Henchy, 2013;Kampf & Teske, 2013;Khan et al, 2012;Kim et al, 2016;Makubuya et al, 2020Vasold, et al, 2019Yigiter & Bayazit, 2013;Zegre et al, 2020).…”
Section: Introductionmentioning
confidence: 91%
“…This is supported by Kim et al (2016) suggestion that students who participate in university sports are more likely to transfer skills and character traits such as integrity, commitment, and work ethics learned from sports into their career fields. More benefits associated with sports participation by university students include; improved physical fitness, high self-esteem, better academic performance, and enhanced mental and social development (Coenders et al, 2017;Diehl et al, 2018;Forrester, 2015;Henchy, 2013;Kampf & Teske, 2013;Khan et al, 2012;Kim et al, 2016;Makubuya et al, 2020Vasold, et al, 2019Yigiter & Bayazit, 2013;Zegre et al, 2020). Additionally, if sports participation is maintained, the benefits lead to good health and well-being of students throughout their life on campus and even after graduation (Henchy, 2013).…”
Section: Introductionmentioning
confidence: 91%